The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.3147/jsfp.41.29
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Hemagglutinating Activity of Edwardsiella tarda by Sodium Chloride

Abstract: ABSTRACT-The hemagglutinating activity (HA) of Edwardsiella tarda, which had been isolated from cultured fish and culture environments, was investigated in relation to NaCl concentration of the growth medium. E. tarda cells were cultured in a peptone-yeast extract broth supplemented with 3% NaCl (3%-NaCl culture) and without NaCl (0%-NaCl culture). Hemagglutination assays with guinea pig erythrocytes classified the strains into three HA patterns. Seventeen strains exhibited HA only with the 3%-NaCl culture (ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 35 publications
(32 reference statements)
3
15
0
Order By: Relevance
“…In the present study, we demonstrated that the adhesive patterns of E. tarda strains to HEp-2 cells well correlated with their HA patterns against guinea pig erythrocytes described previously, where the HA of E. tarda FK1051 and KG8401 was enhanced by the increase of NaCl concentration in the culture media (Yasunobu et al, 2006). The NaClinduced adherence was also described in Salmonella typhi (Tartera and Metcalf, 1993), in which the adherence ability to Henle 407 epithelial cells increased under higher osmolarity (until 0.3 M NaCl) of the culture medium.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In the present study, we demonstrated that the adhesive patterns of E. tarda strains to HEp-2 cells well correlated with their HA patterns against guinea pig erythrocytes described previously, where the HA of E. tarda FK1051 and KG8401 was enhanced by the increase of NaCl concentration in the culture media (Yasunobu et al, 2006). The NaClinduced adherence was also described in Salmonella typhi (Tartera and Metcalf, 1993), in which the adherence ability to Henle 407 epithelial cells increased under higher osmolarity (until 0.3 M NaCl) of the culture medium.…”
Section: Discussionsupporting
confidence: 87%
“…The NaClinduced adherence was also described in Salmonella typhi (Tartera and Metcalf, 1993), in which the adherence ability to Henle 407 epithelial cells increased under higher osmolarity (until 0.3 M NaCl) of the culture medium. Our previous infection experiments with E. tarda FK1051 showed that the 3%-NaCl culture was more virulent to Japanese founder than the 0%-NaCl culture, when fish were challenged orally, and thus we speculated that NaCl-induction of HA is important for adherence of E. tarda to the intestinal epithelial cells of fish (Yasunobu et al 2006). The present result, i.e.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations